2010
DOI: 10.14411/eje.2010.006
|View full text |Cite
|
Sign up to set email alerts
|

Speed or sperm: A potential trade-off between development and reproduction in the butterfly, Bicyclus anynana (Lepidoptera: Nymphalidae)

Abstract: Abstract. Life-history theory predicts trade-offs between resources invested in reproduction and other fitness-related traits. To date, most studies have focused on potential reproductive trade-offs in females. However, it is now generally accepted that reproduction is also costly for males, and thus males too may be subject to trade-offs. We examined the relationship between development time and the production of both fertile and non-fertile sperm in males of the African bush brown butterfly (Bicyclus anynana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 33 publications
2
10
0
Order By: Relevance
“…In the development of M. sexmaculatus and P. dissecta, there exists an inherent variation in developmental rate (i.e., slow and fast) within a cohort placed at a constant condition. The coexistence of two rates of development within a cohort has also been reported previously in a few organisms (Gross, 1985;Thomas et al, 1998;Schönrogge et al, 2000;Skorping, 2007;Lewis et al, 2010) including insects (Gouws et al, 2011), chrysomelid, Z. bicolorata (Pandey et al, 2013), and ladybirds (Mishra & Omkar, 2012;Singh et al, 2014). The rationale behind the variation in developmental rate could be: (i) difference in maternal investment (Osawa, 2003), (ii) asynchronization in hatching (Kawai, 1978;Osawa, 1992), (iii) eggs with different metabolic rates due to allelic differences (Osawa & Ohashi, 2008;Sloggett & Lorenz, 2008), and/or (iv) mother laying eggs with different sizes and nutritional content (Hodek et al, 2012).…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…In the development of M. sexmaculatus and P. dissecta, there exists an inherent variation in developmental rate (i.e., slow and fast) within a cohort placed at a constant condition. The coexistence of two rates of development within a cohort has also been reported previously in a few organisms (Gross, 1985;Thomas et al, 1998;Schönrogge et al, 2000;Skorping, 2007;Lewis et al, 2010) including insects (Gouws et al, 2011), chrysomelid, Z. bicolorata (Pandey et al, 2013), and ladybirds (Mishra & Omkar, 2012;Singh et al, 2014). The rationale behind the variation in developmental rate could be: (i) difference in maternal investment (Osawa, 2003), (ii) asynchronization in hatching (Kawai, 1978;Osawa, 1992), (iii) eggs with different metabolic rates due to allelic differences (Osawa & Ohashi, 2008;Sloggett & Lorenz, 2008), and/or (iv) mother laying eggs with different sizes and nutritional content (Hodek et al, 2012).…”
Section: Discussionsupporting
confidence: 78%
“…Large-sized males supply better quality of genes in addition to accessory gland proteins (Avila et al, 2011;Hanin et al, 2011;Helinski & Harrington, 2011). Lewis et al (2010) reported that the slow developing Values are mean ± SE. For both ladybird species, lower cases represent comparison of means between slow and fast developing individuals within ladybird species at each photoperiod, and upper cases in parentheses represent comparison of means between slow and fast developing individuals within ladybird species at different photoperiods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…a longer development time, hence slower development, results in an increased fecundity) (e.g. Nunney 1996; Tsikliras, Antonopoulou et al 2007; Lewis, Brakefield et al 2010; Yadav and Sharma 2014). This trade-off can be mediated through a positive correlation between development time and adult size ( e.g .…”
Section: Online Supplementary Materialsmentioning
confidence: 99%
“…(), however, showed that females did not reject sperm‐depleted males before mating. This behaviour is probably similar to the production of non‐fertile sperm at a high rate by male butterflies (Lewis et al ., ), and would be involved in male competition. Moreover, in other parasitoid species, such as Nasonia vitripennis (Chirault et al ., ) or Dinarmus basalis (Lacoume, Bressac & Chevrier, ), it has been shown that environmental stresses such as heat or cold produced sperm‐depleted males, which females do not reject.…”
Section: Discussionmentioning
confidence: 99%